Antimicrobial prescriptions in cats in Switzerland before and after the introduction of an online antimicrobial stewardship tool - Hubbuch, Alina (BMC Vet Res, 2020)
BACKGROUND: Antimicrobial stewardship activities are essential to improve prudent antimicrobial use. The aim of the present study was to evaluate changes in antimicrobial prescriptions in cats after the introduction of prudent use guidelines promoted by an online antimicrobial stewardship tool (AntibioticScout.ch) in Switzerland. Data from 792 cats presented to two university hospitals and 14 private practices in 2018 were included and compared to 776 cases from 2016. Cats were diagnosed with acute upper respiratory tract disease (aURTD), feline lower urinary tract disease (FLUTD) and abscesses. Clinical history, diagnostic work-up and antimicrobial prescriptions (class, dosage, duration) were assessed. Type and proportions [95% confidence intervals] of antimicrobial prescriptions were compared between the two evaluation periods and a mixed effects logistic regression model was applied to evaluate compliance with Swiss prudent use guidelines. RESULTS: From 2016 to 2018, the proportion of antimicrobial prescription in all included cases decreased from 75.0% [71.8–78.0] to 66.7% [63.3–69.9]; this decrease was most pronounced for treatments at university hospitals (67.1% [59.5–74.0] to 49.3% [40.9–57.8]) and for cats with FLUTD (60.1% [54.6–65.4] to 48.8% [43.2–54.4]). Use of 3rd generation cephalosporins in private practices declined from 30.7% [26.5–35.1] to 22.1% [18.4–26.2], while overall use of non-potentiated aminopenicillins increased from 19.6% [16.4–23.0] to 27.8% [24.1–31.9]. In cases where antimicrobial therapy was indicated, compliance with guidelines did not increase (33.3% [26.6–40.6] to 33.5% [27.2–40.2]), neither at universities nor in private practices. On the other hand, antimicrobial treatment was more often withheld in cases with no indication for antimicrobial therapy (35.6% [30.1–41.4] to 54.0% [47.6–60.4]); this was found for private practices (26.7% [20.8–33.4] to 46.0% [38.4–53.7]) and for aURTD cases (35.0% [26.5–44.2] to 55.4% [44.7–65.8]). CONCLUSIONS: Overall proportions of antimicrobial prescription, unjustified antimicrobial therapy and, in private practices, use of 3rd generation cephalosporins decreased from 2016 to 2018 for the investigated feline diseases. However, overall compliance with Swiss prudent use guidelines was still low, implying that further efforts are required to foster prudent antimicrobial use in cats.